2014
DOI: 10.3992/1943-4618-9.3.85
|View full text |Cite
|
Sign up to set email alerts
|

Can Greenwalls Contribute to Stormwater Management? A Study of Cistern Storage Greenwall First Flush Capture

Abstract: The authors set out to study the stormwater management viability of greenwalls in a simulated retention of roof runoff, using a cistern for simulated runoff to irrigate the greenwalls. By experimenting with two greenwalls of different exposures (one southeast and one northwest), this study demonstrated that the southeast facing greenwall and the northwest facing greenwall retained comparably favorable amounts to greenroof stormwater retention systems. With more and more competition for limited horizontal surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 13 publications
2
14
0
Order By: Relevance
“…This observed delay in precipitation reaching the ground surface is broadly speaking, in line with a previous observation for a green roof, which concluded that nearly two thirds of all the precipitation events resulted in runoff delays of a minimum of 30-minutes (Czemiel Berndtsson, 2010). However, given the faster flow under gravity in a vertical green façade, its delay should be lower than in a green roof (Kew et al, 2014). Retention of a proportion of precipitation in this manner, and its eventual evaporation and transpiration, and the delay associated with flow through the system, can potentially reduce the peak flows and the consequential overwhelming of urban drainage infrastructure (Czemiel Berndtsson, 2010;Loh, 2008).…”
Section: Façade Precipitation Interceptionsupporting
confidence: 90%
See 4 more Smart Citations
“…This observed delay in precipitation reaching the ground surface is broadly speaking, in line with a previous observation for a green roof, which concluded that nearly two thirds of all the precipitation events resulted in runoff delays of a minimum of 30-minutes (Czemiel Berndtsson, 2010). However, given the faster flow under gravity in a vertical green façade, its delay should be lower than in a green roof (Kew et al, 2014). Retention of a proportion of precipitation in this manner, and its eventual evaporation and transpiration, and the delay associated with flow through the system, can potentially reduce the peak flows and the consequential overwhelming of urban drainage infrastructure (Czemiel Berndtsson, 2010;Loh, 2008).…”
Section: Façade Precipitation Interceptionsupporting
confidence: 90%
“…This can be attributed to the tall, thin, vertical nature of the façade which creates a dense canopy, capable of holding quite a lot of water. In general, the findings corroborate previous studies suggesting the proportion of precipitation interception is directly proportional to the vegetation cover (Czemiel Berndtsson, 2010;Kew et al, 2014;Natarajan et al, 2015). The vegetation cover is linked to the extent to which the building façade is enveloped, and dictates its ability to retain and prevent precipitation from entering drainage infrastructure.…”
Section: Façade Precipitation Interceptionsupporting
confidence: 89%
See 3 more Smart Citations